The important points to anesthesiologist in cardiac physiology [Kalbin Fizyolojisinde Anestezistler Açisindan Önemli Noktalar] - (:unkn) unknown (Turkish Anaesthesiology and Intensive Care Society, 2015)
Anesthesia affects the physiology of each patient and most especially the cardiovascular system is affected. Therefore understanding the physiology of the cardiovascular system allows a better understanding of the changes occurring under anesthesia, enabling recognition and effective treatment of the adverse events. This review has addressed the points that are important to anesthesiologists in cardiac physiology.
Keywords: Anesthesia; Cardiac ischemia; Cardiac physiology